A Conceptual Framework of MkIS Design: the Impact of Environmental Uncertainty Perceptions, Decision-Maker Characteristics and Work Environment Factors on the Perceived Usefulness of Marketing Information Characteristics - Ashill, Nicholas; Jobber, David (School of Management Working Papers, 1999)
This paper discusses potential relationships between contextual factors and Marketing Information Systems (MkIS) design. MkIS design is defined in terms of the perceived usefulness of several information characteristics, which may be associated with a marketing information system. The paper suggests that MkIS design research should consider a range of contextual variables drawn from the organisational behaviour, behavioural decision-making and personality/cognitive psychology literatures. Drawing on empirical results from three sets of literature and from studies of information systems design (particularly management and accounting information systems design), the authors present a framework for exploring the design of a MkIS.